(untitled) (CIPEEX, 2023)
Autism is considered a complex syndrome that involves developmental deviations from the early years of life in the areas of social interaction, communication, and behavior, with multiple causes and manifestations that encompass a wide variability of symptoms and responses to interventions. It was initially described by the Austrian psychiatrist LeoKanner in 1943, based on the cases of 11 children he was observing who exhibited impairments in three areas: social relationships, communication/language, and behavior. The author stated that individuals with autism had an innate inability to emotionally relate to other people, which would depend on a biological aspect. Due to the increasing number of cases of children with Autism Spectrum Disorder (ASD) and their relationship with the process of inclusion and belonging, the objective of this research was to describe and update the methodological bibliographic field in the relationship between ASD and topophilia. Understanding the theoretical-methodological concepts is of fundamental importance to subsequently evaluate the participation of the actors in theschool unit to promote the school inclusion of autistic children, which occurs through the effective participation of the parties.